Acceptance of COVID-19 vaccine and determinant factors in the Iranian population: a web-based study - Shabnam Omidvar; Mojgan Firouzbakht (BMC, 2022)
Abstract Background Iran had a high rate of death in several COVID 19 waves. Vaccination is a method for prevention and control of the COVID-19 pandemic. Success in controlling the pandemic is not solely dependent on the effectiveness of the vaccines. It is also dependent on the global acceptance and vaccine coverage rate. This study aimed to determine the acceptance rate of COVID-19 vaccination in the Iranian population and the factors affecting it. Methods and materials This study was a cross-sectional research on 1564 Iranian people above 18. Study data were collected using a web-based questionnaire and analyzed using linear regression analysis and logistics at a significance level of 0.05 using SPSS. Results Approximately 70% of the participants reported acceptance of the vaccines. Ten percent of the people were against and 20% were hesitant to get vaccinated. The results showed that risk perception (P = .003), Knowledge of the disease (P < .001), trust in the health system (P < .001), attitude towards vaccination (P < .001), and vaccination literacy (P < .001) were predictors of vaccine acceptance. People with higher levels of education and mistrust towards the health system had a reduced vaccine acceptance rate. Conclusions The acceptance rate of the COVID-19 vaccine in Iran was higher than in the other countries in the Middle East. Extensive interventions are important to increase the trust in the health system and improve the knowledge of vaccine efficacy and literacy.